Variable coverage in an Autocidal Gravid Ovitrap intervention impacts efficacy of Aedes aegypti control. Issue 10 (13th July 2021) - Juarez, Jose G.; Chaves, Luis F.; Garcia‐Luna, Selene M.; Martin, Estelle; Badillo‐Vargas, Ismael; Medeiros, Matthew C. I.; Hamer, Gabriel L.
Abstract: Control of the arboviral disease vector Aedes aegypti has shown variable levels of efficacy around the globe. We evaluated an Autocidal Gravid Ovitrap (AGO) intervention as a stand‐alone control tool for population suppression of A . aegypti in US communities bordering Mexico. We conducted a cluster randomized crossover trial with weekly mosquito surveillance of sentinel households from July 2017 to December 2018. The intervention took place from August to December of both years. Multilevel models (generalized linear and additive mixed models) were used to analyse the changes in population abundance of female A . aegypti . We observed that female populations were being suppressed 77% (2018) and four times lower outdoor female abundance when AGO coverage (number of intervention AGO traps that surrounded a sentinel home) was high (2.7 AGOs/house). However, we also observed that areas with low intervention AGO coverage resulted in no difference (2017) or slightly higher abundance compared to the control. These results suggest that coverage rate might play a critical role on how populations of female A . aegypti are being modulated in the field. The lack of larval source habitat reduction and the short duration of the intervention period might have limited the A . aegypti population suppression observed in this study. Synthesis and applications . The mosquito, A . aegypti, is a public health concern in most tropical and subtropical regions. With the rise of insecticide resistance, the evaluation of non‐chemical tools has become pivotal in the fight against arboviral disease transmission. Our study shows that the AGO intervention, as a stand‐alone control tool, is limited by its coverage in human settlements. Vector control programmes should consider, that if the target coverage rate is not achieved, measures will be ineffective unless coupled with other control approaches. Although our multilevel modelling was focused on A . aegypti and the AGO, the approach can be applied to other mosquito vector species. Abstract : The mosquito, A . aegypti, is a public health concern in most tropical and subtropical regions. With the rise of insecticide resistance, the evaluation of non‐chemical tools has become pivotal in the fight against arboviral disease transmission. Our study shows that the AGO intervention, as a stand‐alone control tool, is limited by its coverage in human settlements. Vector control programmes should consider, that if the target coverage rate is not achieved, measures will be ineffective unless coupled with other control approaches. Although our multilevel modelling was focused on A . aegypti and the AGO, the approach can be applied to other mosquito vector species.